Implementation of the Pancasila Student Profile Strengthening Project in History Education at Palu State Senior High School 4 - Nengsi Rindanita; Iskandar Iskandar; Suyuti Suyuti; Minarni Nongtji (Journal of Educational Sciences, 2026)
This study aims to analyze the application of the Pancasila Student Profile dimensions in history learning and to identify the supporting and inhibiting factors in the implementation of the Pancasila Student Profile Strengthening Project (P5) at SMA Negeri 4 Palu. The study used a qualitative approach with a descriptive method. Data were obtained through observation, interviews, and documentation of the vice principal for curriculum and history teachers. The results show that the implementation of the six dimensions of the Pancasila Student Profile, namely faith and noble character, global diversity, mutual cooperation, independence, critical thinking, and creativity, has been integrated into history learning through discussions, event analysis, and project-based activities such as clippings, debates, and the creation of replicas of historical objects. The dimension of mutual cooperation was the easiest to implement because it was supported by group work, while critical thinking was a challenge due to differences in students' analytical abilities. Supporting factors included school management support, teacher collaboration, training, and the availability of facilities. Meanwhile, inhibiting factors include time constraints, the influence of globalization and technology, and disparities in student abilities. Overall, the implementation of P5 contributes positively to shaping the character and competencies of students in accordance with the values of Pancasila.